Strategi Digital Marketing Dalam Meningkatkan School Branding Di Man 1 OKU Timur - Ayu Lestari; Finani (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang OKU Timur Sumatera Selatan, 2026)
This study aims to describe in depth the digital marketing strategy implemented by MAN 1 OKU Timur in an effort to improve school branding as a competitive educational institution. The background of this study departs from the development of information technology that requires schools to be adaptive to digital transformation, especially in the field of promotion and publication, so that they can build a positive image in the community. This study uses a qualitative approach with a descriptive method, where data is collected through purposive sampling and snowball sampling techniques to obtain information from relevant sources. Data collection techniques include observation of school activities, in-depth interviews with related parties such as the principal, teachers, staff, students, and the community, as well as documentation studies in the form of archives, photos, and school digital content. Data analysis is carried out through the process of data reduction, data presentation, and drawing conclusions, while the validity of the data is checked by the method of source triangulation and method triangulation. as a means of school promotion, but also as a form of providing identity and strengthening the positive image of the school in the eyes of the community. The results of the study conducted at MAN 1 OKU Timur show that the digital marketing strategy in improving school branding has been implemented well, this is indicated by the management carried out by the school. Several digital marketing strategies of MAN 1 OKU Timur are: a) Website, b) Instagram, c) Facebook, d) Tiktok, e) Youtube. The implementation of these digital marketing strategies is supported by various factors, both inhibiting and supporting factors. Inhibiting factors include limited school budget, lack of human resources who master digital technology, low understanding of some teachers and students regarding digital literacy, and lack of student involvement in the media management process. Meanwhile, supporting factors consist of the quality of professional educators and education staff, the availability of supporting facilities and infrastructure, and the support and participation of the community who entrust their children's education to the school. Overall, this study concludes that digital marketing strategies can have a positive impact on improving the school branding of MAN 1 OKU Timur. This is reflected in the increasing recognition of the school in the community, the increasing positive image of the school, and the involvement of various parties in supporting the publication of activities and achievements. Thus, digital marketing is not only a promotional medium, but also an important instrument in building the reputation and competitiveness of schools in the modern era. The results of this study found that digital marketing strategies have a positive impact on improving the school branding of MAN 1 OKU Timur.